2019
DOI: 10.1101/791046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of the coordination between host circadian rhythms and malaria parasite development alters the duration of the intraerythrocytic cycle

Abstract: Malaria parasites complete their intra-erythrocytic developmental cycle (IDC) in multiples of 24 hours (depending on the species), suggesting a circadian basis to the asexual cell cycle, but the mechanism controlling this periodicity is unknown.Combining in vivo and in vitro approaches using rodent and human malaria parasites, we reveal that: (i) 57% of Plasmodium chabaudi genes exhibit 24 h "circadian" periodicity in transcription; (ii) 58% of these genes lose transcriptional rhythmicity when the IDC is out-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…of parasites in vivo are inevitably confounded by synchronous development throughout the IDC of 24 h. Using P. falciparum would overcome some of these obstacles because its IDC duration is 48 h and it can be cultivated in vitro (Subudhi et al, 2019). Thus, experiments in which constant (''free-running'') conditions are generated by either not replenishing or continuously replenishing media could use P. falciparum to test for 24 h rhythms in gene expression and protein production, as well as temperature compensation.…”
Section: Can Parasites Keep Time?mentioning
confidence: 99%
“…of parasites in vivo are inevitably confounded by synchronous development throughout the IDC of 24 h. Using P. falciparum would overcome some of these obstacles because its IDC duration is 48 h and it can be cultivated in vitro (Subudhi et al, 2019). Thus, experiments in which constant (''free-running'') conditions are generated by either not replenishing or continuously replenishing media could use P. falciparum to test for 24 h rhythms in gene expression and protein production, as well as temperature compensation.…”
Section: Can Parasites Keep Time?mentioning
confidence: 99%
“…A recent report has addressed a similar question in Plasmodium (Subudhi et al, 2019). Mice infected with P. chabaudi (which displays a 24 h development cycle in RBCs) were housed under a light-dark cycle, and blood sampled over 30 h was used for RNA sequencing: over 5,000 P. chabaudi transcripts displayed ∼24 h rhythms.…”
Section: Evidence For Circadian Timing Mechanisms Within Parasitesmentioning
confidence: 99%
“…A followup study showed that this mismatch effect does not depend on either the developmental stage of the parasite used for infection or on the route of infection, and has an impact at early infection stages (O'Donnell et al, 2013). A misalignment of the P. chabaudi and host rhythms also impacted rhythmic parasite genes, and led to a reduced development cycle period (Subudhi et al, 2019).…”
Section: Misalignment Of Host-parasite Rhythmsmentioning
confidence: 99%